Decompositions of λ-fold complete bipartite 3-uniform hypergraphs λKn,n(3) into hypergraph K4(3) - e - Zhao, Hongtao,; Zhang, Qingyun, (Utilitas Mathematica, 2020)
In this paper, we consider one type of hypergraph decompositions. We show that a (K4(3) - e)-decomposition of a λ-fold complete bipartite 3-uniform hypergraph λKn,n(3) exists if and only if 3|λn2(n - 1) and n ≥ 2. © 2020 Utilitas Mathematica Publishing Inc.. All rights reserved.